(untitled) (The Pakistan Development Review, 1999)
The positive role of women in economic development cannot be understated; those that are educated and properly empowered can act as catalysts in the development process. This book is about how to empower women so that they can become independent and self-sustaining actors in development. The conventional wisdom is that womens’ empowerment depends on following a simple strategy—alleviate poverty by spending large amounts of money. Having followed this strategy in the past the author feels that it has been far from successful. Monetary inputs by itself is not a sufficient condition to assist women in improving their status. The author puts forward an alternate view that the reasons why women are disadvantaged in India, despite fifty years of development, is due to their ignorance, powerlessness and vulnerability. This is particularly so for those women who belong to the Scheduled Castes (Harijans) and Scheduled Tribes (Girijans or “mountain people”).